Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Mata Kuliah Pengantar Ilmu Politik - Polii, E. H. (Academy of Education Journal, 2024)
This research aims to assess the impact of using the jigsaw cooperative learning model on students' achievements in the Introduction to Political Science course. The study employs a quantitative method with a quasi-experimental design. The research population includes all students in class AB, Semester I, 2023 intake, majoring in Public Administration at Manado State University, totaling 50 individuals. The research sample consists of students in class A as the experimental group, implementing the jigsaw cooperative learning model, and class B as the control group, using the conventional model. The research findings indicate that the use of the jigsaw cooperative learning model has a positive effect on students' understanding of government system materials compared to the conventional method. The data analysis results, using paired sample t-test for output pair 1 with a Sig. (2-tailed) value of 0.000 < 0.05, lead to the conclusion that there is an influence of the jigsaw cooperative learning model on students' learning outcomes in the Introduction to Political Science course.